Development and validation of a table tennis serve skill assessment instrument for junior high school students: A psychometric approach - Muhammad Aliffajaruddin Alfani; M. E. Winarno; Siti Nurrochmah (Physical Education and Sports, 2025)
Background: The highest assessment weight in physical education lessons lies in psychomotor skills. In order to find out how far the competencies possessed by students, a clear and comprehensive assessment tool or instrument is needed.